A Prospective, Multicenter, Open-Label Study of Dose Escalation Therapy in Male Patients With Nocturia Refractory to 0.2-mg Tamsulosin Monotherapy - Yu, Ho Song (Int Neurourol J, 2019)
PURPOSE: To investigate the efficacy and safety of 0.4 mg of tamsulosin in patients with nocturia not responding to 0.2 mg. METHODS: Patients with intractable nocturia after treatment with 0.2 mg of tamsulosin for>1 month were included in a multicenter, prospective, observational, single-arm study. Patients were prescribed 0.4 mg of tamsulosin and followed up for 2 months to assess nocturnal voiding and nocturia-related bother. Changes in the mean number of nocturnal voids, the proportion of 50% responders, 3-day frequency-volume chart parameters, and questionnaire scores were assessed. RESULTS: Sixty-two patients were prescribed 0.2 mg of tamsulosin, of whom 56 were prescribed 0.4 mg of tamsulosin. Ten patients dropped out. A single case of orthostatic hypotension was reported. The mean age was 68 years. After 1 and 2 months of taking 0.4 mg of tamsulosin, 23.9% and 22.7% of patients demonstrated a>50% reduction of nocturia, and 16.1% and 19.4% of patients rated the treatment as “very effective,” respectively. Dose escalation to 0.4 mg of tamsulosin, compared to 0.2 mg, did not show an additional effect on reducing nocturnal urine volume. Multivariate logistic regression analysis showed that lower serum sodium levels (odds ratio [OR], 0.41, P=0.037) and the presence of urge incontinence (OR, 7.08, P=0.036) were predictors of a significant improvement of nocturia in response to 0.4 mg of tamsulosin. CONCLUSIONS: Dose escalation may yield a significant improvement of nocturia in>20% of patients, and may be especially helpful in patients with lower sodium levels and urge incontinence.